(untitled) (Research, Society and Development, 2021)
Ergology is the scientific and philosophical perspective that studies human work seeking to contemplate human activity in all its dimensions, based on the project of better knowing the work to intervene and transform it. This is an integrative literature review study whose objective was to discuss and reflect on Ergology as a theoretical framework and its contributions to health work and radiological protection. Ergology as theoretical framework is of extreme importance and practical application. It is necessary to intensify the execution of its practices in research and in the applicability in Radiological Protection, expanding and maximizing the quality of care provided to patients as well as the quality of life of workers and users in health services.